Risk factors and predictors of recurrence of febrile seizures in children in Nantong, China: a retrospective cohort study - Feifei Shen; Leijuan Lu; Youjia Wu; Guihai Suo; Yuqin Zheng; Xiuli Zhong; Xu Wang; Haiying Li (BMC, 2024)
Abstract Background Although most children with febrile seizures (FS) have a favorable prognosis, some experience recurrence within 1-3 years. Age, peak temperature, and family history are now recognized as important risk factors for FS recurrence, yet studies in this area are lacking in China. This study aimed to investigate the risk factors for FS recurrence in children in Nantong, China, and to develop a prediction model. Methods This retrospective cohort study analyzed 463 children diagnosed with febrile seizures (FS) who presented to the Affiliated Hospital of Nantong University between January 2015 and June 2020. Basic information, disease characteristics, and laboratory and imaging data were collected. A follow-up survey was conducted one year post-discharge to assess the recurrence status of FS in children. Univariate logistic regression and random forest models were used to identify and rank the predictive ability of risk factors for recurrence. Results Of the 463 children with FS, 70 experienced recurrences within 1 year of discharge, resulting in a one-year recurrence rate of 15%. Age (OR = 0.61, 95% CI: 0.46, 0.80, P < 0.001), duration of the first episode (OR = 1.03, 95% CI: 1.00, 1.06, P = 0.040), and peak temperature (OR = 0.68, 95% CI: 0.47, 0.98, P = 0.036) were identified as independent risk factors for FS recurrence. Age had the highest relative importance in predicting FS recurrence, followed by the duration of the first episode, with an area under the ROC curve of 0.717. Conclusion Young age and duration of the first seizure are important independent risk factors for FS recurrence and are key considerations for predicting recurrence. Further research is needed to confirm the potential use of Neutrophil-lymphocyte ratio (NLR) as a predictor of FS recurrence.